A Two-wave Longitudinal Study of Identity Profiles Based on Eight Dimensions: Further Insight into Exploration and Commitment Quality as Well as Life Domains Central to Identity. Issue 2 (3rd April 2021) - Mannerström, Rasmus; Hietajärvi, Lauri; Salmela-Aro, Katariina
ABSTRACT: It has been suggested that dual-cycle models of identity formation do not fit well with Erikson's identity theory and the identity status paradigm due to 1) contradictory statuses, 2) problems with discerning past exploration and 3) ambiguity or limitations of the life domains covered. The present study extended the Dimensions for Identity Development Scale (DIDS) with three additional dimensions suggested previously, examined identity profiles and their transitions over time, their links with psychological well-being and what life domain was associated with "future plans" (N=1294; T1: age=17, 60% female; T2: age=18, 65% female). The results showed that 1) the eight-dimensional model fit the data well longitudinally; 2) six previously reported profiles emerged at both time points with expected links to psychological well-being; 3) as previously speculated, individuals in the (early) closure status had undertaken identity exploration in the past; 4) the previously encountered high commitment-high exploration status (i.e., searching moratorium) seems to be "superficially committed"; and 5) future plans are commonly associated with work life/occupation. Future research would benefit from employing qualitative research to better understand the subjective meanings attached to high commitment-high exploration and by developing new ways to account for quality and different levels of commitment.